Accrual earnings management: Evidence from IPOs firms in Indonesia - Januri (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2021)
This study aims to analyze the influence of information asymmetry and managerial ownership toward earnings management with audit committee as moderating variable. This research used 119 companies which did Initial Public Offering (IPOs) during the period of 2014 to 2018. The data were analyzed using moderate regression analysis (MRA). This research used audit committee as moderating variable to analyze the influence of information asymmetry and managerial ownership toward earnings management. The results showed that the information asymmetry and managerial ownership had negative significant influence toward earnings management. The audit committee was unable to moderate the influence of information asymmetry and managerial ownership toward earnings management. Investors must prioritize vigilance in considering investment decisions, and more explore deeply into the company’s characteristics, especially since the company has just gone public.